If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(8 + -1x) + 1 = 13 (8 * 4 + -1x * 4) + 1 = 13 (32 + -4x) + 1 = 13 Reorder the terms: 32 + 1 + -4x = 13 Combine like terms: 32 + 1 = 33 33 + -4x = 13 Solving 33 + -4x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + -33 + -4x = 13 + -33 Combine like terms: 33 + -33 = 0 0 + -4x = 13 + -33 -4x = 13 + -33 Combine like terms: 13 + -33 = -20 -4x = -20 Divide each side by '-4'. x = 5 Simplifying x = 5
| t+-218=376 | | (3i)(6i)= | | -9d=783 | | 4x+10+3x-5+x-5=180 | | b+-585=9 | | 80+4x-140=180 | | m-25=-8 | | 1.5x+13=2.4+4 | | 8+3z=17 | | log14/x=2 | | 2/3x-5/6x=1 | | (15m2)1/3 | | 45=r-14 | | log8/x=2 | | 5-2k=3 | | 8a+2b-5c+10= | | 6x-16=3x-54 | | n/4=86/344 | | 2p=70 | | X-5+3x-5+4x+10=180 | | -u=61 | | x^2-24=-10x | | 8(x-5)-3=26x-187 | | 21.3+p=30 | | x^2-9y^2-6x-36y-36=0 | | m+10=-78 | | 5(3x-10)=130 | | -24=g+-68 | | m+16=35 | | 2x+3ky+6=0 | | p+-10=-52 | | f-92=7 |